Achievement at whose expense? A literature review of test-based grade retention policies in U.S. school - Huddleston, Andrew Prescott (Education Policy Analysis Archives, 2014)
The author uses Maxwell’s method of literature reviews for educational research to focus on literature relevant to test-based grade retention policies to make the following argument: although some studies have documented average gains in academic achievement through test-based grade retention, there is increasing evidence that these gains have occurred by limiting the educational opportunities for the most vulnerable of students. The author begins by briefly synthesizing research on high-stakes testing policies and teacher-based retention in general and then examines studies that have evaluated specific test-based retention policies in Chicago, Florida, New York City, Georgia, Texas, Wisconsin, and Louisiana. Drawing on Bourdieu and Passeron’s concept of reproduction in education, the author shows how testing policies have contributed to class selection and exclusion in U.S. schools. Short-term gains produced by test-based retention policies fade over time with students again falling behind but with a larger likelihood of dropping out of school. These unintended consequences are most prevalent among ethnic minority and impoverished students. The author concludes by providing alternatives for ending social promotion that do not include grade retention as well as suggestions for further researching the role such policies play in perpetuating class inequities.